2022
DOI: 10.3390/life12020150
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Potential of Vimentin in Oral Cancers

Abstract: Oral carcinogenesis is a multistep process. As much as 5% to 85% of oral tumors can develop from potentially malignant disorders (PMD). Although the oral cavity is accessible for visual examination, the ability of current clinical or histological methods to predict the lesions that can progress to malignancy is limited. Thus, developing biological markers that will serve as an adjunct to histodiagnosis has become essential. Our previous studies comprehensively demonstrated that aberrant vimentin expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Consistent with these studies, we have demonstrated that vimentin regulates differentiation switching via the modulation of K5/14 transcript levels, perhaps via ΔNP63 signaling. The expression of K5/14 and vimentin correlated with a poor prognosis of oral cancer patients [ 56 , 57 ].…”
Section: Aberrant Expression Of Keratins In Osccmentioning
confidence: 99%
“…Consistent with these studies, we have demonstrated that vimentin regulates differentiation switching via the modulation of K5/14 transcript levels, perhaps via ΔNP63 signaling. The expression of K5/14 and vimentin correlated with a poor prognosis of oral cancer patients [ 56 , 57 ].…”
Section: Aberrant Expression Of Keratins In Osccmentioning
confidence: 99%
“…Vimentin is crucial for the EMT, metastasis, and invasion of mesenchymal cells ( Satelli and Li, 2011 ; Usman et al, 2021 ). Hence, no wonder that most studies designated the significance of vimentin as a biomarker in cancers with clinical relevance in several types of cancers ( Ben-Ze’ev and Raz, 1985 ; Hu et al, 2004 ; Jin et al, 2010 ; Li M. et al, 2010 ; Wei et al, 2008 ; Bogush et al, 2020 ) and the more in depth information can be found elsewhere ( Satelli and Li, 2011 ; Zhao et al, 2013 ; Polioudaki et al, 2015 ; Mogre et al, 2022 ). In lung cancers, vimentin has been shown to be the target of various regulating factors that control expression or cause post-translational modification of vimentin.…”
Section: Vimentin Intermediate Filaments In Pathological Roles In Lun...mentioning
confidence: 99%